O batismo de crianças celebrado no "aricuri" no caminho de afirmação Pipipã (Floresta - PE): um estudo de caso - Reani, Alberto (2017)
The path of Pipipã affirmation is expressed through multiple choices such as: internal organization, indigenous schools (differentiated education), aricuri resumption with its spiritual and “diacritical” meaning, construction of the Saint Expedite's Chapel and organization of children's baptism in aricuri. This research sought to interpret the meaning of these aspects in the perspective of the “way back”, the affirmation of the identity of the Pipipã indigenous people (município de Floresta, Sertão de Pernambuco). A participant research was carried out as an instrument of data collection and construction of “intercultural dialogue”, having theoretical foundations and reflections on Anthropology and History, which became important tools to analyze the Pipipã people's project. Children's baptism celebration in aricuri context is a kind of meeting point of two intentionalities: that of Pipipã on his “way back”, and that of the Vatican Council II in his desire to reform the Liturgy in the perspective of individuals participation with different socio-cultural expressions.